RISK STRATIFICATION OF NUTRITIONAL DEFICIENCY IN INFANTS WITH CONGENITAL HEART DEFECTS USING WHO ANTHRO AND STRONGKIDS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In recent years, nutritional deficiency in children with congenital heart defects (CHD) complicated by chronic heart failure (CHF) has become an increasingly relevant issue in pediatric cardiology. This study clearly demonstrates that 74% of infants (n=50) aged 1 to 12 months had WHO Anthro Z-scores below –2 SD, and 38% were below –3 SD, indicating severe malnutrition. Furthermore, 56% of the sample comprised infants with cyanotic defects, consistent with Mehta et al. (2013), who noted enhanced catabolism under chronic hypoxia. Biochemical markers revealed hypoproteinemia (5 mg/L) in 22%. Risk stratification using the STRONGkids scale identified high risk of nutritional deficiency in 62% of patients, aligning with the findings of Joosten & Hulst (2014) and Sheveleva & Orlova (2021).